ABDUL-HAMID (IMAM) GHAZALI: IHYA ULUM ID-DIN (REVIVAL OF RELIGIOUS THOUGHT), VOL. 4. DARUL-ISHAAT URDU BAZAR KARACHI-PAKISTAN, 1993 - Choudry, Masud (Journal of Critical Realism in Socio-Economics (JOCRISE), 2024)
This book provides a review of the book “Ihya Ulum Id-Din (Revival of Religious Thought Volume 04)” the work of Islamic scholar Imam Abdul Hamid Al-Ghazali (Imam Ghazali Translated by Fazlul Karim. Darul Ishaat, Urdu Bazar, Karachi, Pakistan, 1993. This is an original contribution, explained in informative content and written in clear language that is accessible to knowledgeable readers